Genome Mining and Characterization of Two Novel Lacticaseibacillus rhamnosus Probiotic Candidates with Bile Salt Hydrolase Activity - Gianluigi Agolino; Marianna Cristofolini; Amanda Vaccalluzzo; Davide Tagliazucchi; Alice Cattivelli; Alessandra Pino; Cinzia Caggia; Lisa Solieri; Cinzia Lucia Randazzo (Biomolecules)
Bile salt hydrolase (BSH; EC 3.5.1.24) is the microbial enzyme that catalyzes the conversion of primary bile acids (BAs) into secondary ones, promoting microbial adaptation and modulating several host’s biological functions. Probiotics with BSH activity are supposed to survive harsh intestinal conditions and exert a cholesterol-lowering effect. Here, Lacticaseibacillus rhamnosus strains (VB4 and VB1), isolated from the vaginal ecosystem, were submitted to a genomic survey, in vitro BSH activity, and BAs tolerance assay to unravel their probiotic potential as BAs modulators. The draft genomes of Lcb. rhamnosus VB4 and VB1 strains comprised 2769 and 2704 CDSs, respectively. Gene annotation revealed numerous strain-specific genes involved in metabolism and transport, as well as in DNA recombination. Each strain harbors a single bsh gene, encoding a C-N amide hydrolase, which conserved the essential residues required in the BSH core site. According to the results, compared to VB1, the VB4 strain tolerated better BAs stress and was more active in deconjugating BAs. However, BAs stress increased the bsh gene transcription in the VB1 strain but not in the VB4 strain, suggesting a partially nonlinear relationship between BSH activity and gene expression. In conclusion, despite the complexity of the BSH transcriptional system, the results support the VB4 strain as a promising BAs-deconjugating probiotic candidate.